A surface-imprinted surface-enhanced Raman scattering sensor for histamine detection based on dual semiconductors and Ag nanoparticles. (1st February 2022) - Chen, Chen; Wang, Ximo; Waterhouse, Geoffrey I.N.; Qiao, Xuguang; Xu, Zhixiang
Highlights: A highly sensitive molecularly imprinted surface-enhanced Raman scattering (SERS) sensor was developed. A combination of dual semiconductors and Ag nanoparticles was used as the SERS substrate. Molecularly imprinted polymers were used as selective recognition elements. This study provide a useful tool for histamine analysis in food products. Abstract: A highly sensitive molecularly imprinted surface-enhanced Raman scattering (SERS) sensor was developed for selective detection of histamine. A combination of two semiconductors and Ag nanoparticles (NPs) was used as the SERS substrate. The SERS was induced by Ag NPs plasmon resonances as well as charge-transfer between the semiconductors and the Ag NPs. The Raman intensity and the logarithm of the histamine concentration were linear over the range 10 −8 –10 −3 mol L −1 . The sensor exhibited good selectivity and had a sensitivity limit of 3.088 × 10 −9 mol L −1 . Histamine was detected in a spiked liquor sample, and its recoveries were in the range of 89.89%–109.18%.